Fate of four phthalate plasticizers under various wastewater treatment processes. Issue 12 (15th October 2018) - Armstrong, Dana L.; Rice, Clifford P.; Ramirez, Mark; Torrents, Alba
ABSTRACT: The fate of four phthalate plasticizers during wastewater treatment processes at six different wastewater treatment plants (WWTPs) was investigated. Concentrations of benzyl butyl phthalate (BBP), di(2-ethylhexyl) phthalate (DEHP), diisononyl phthalate (DiNP), and diisodecyl phthalate (DiDP) were determined prior to either aerobic or anaerobic (conventional and advanced) treatment, after treatment, and in final, dewatered solids. Despite their elevated use worldwide, the fate of DiNP and DiDP during wastewater treatment have not been well characterized. DEHP was readily degraded during aerobic treatments while anaerobic digestion resulted in either no significant change in concentrations or an increase in concentration, in the case of more advanced anaerobic processes (thermal hydrolysis pretreatment and a two-phase acid/gas process). Impacts of the various treatment systems on DiNP, DiDP, and BBP concentrations were more varied – anaerobic digestion led to significant decreases, increases, or no significant change for these compounds, depending on the treatment facility, while aerobic treatment was generally effective at degrading the compounds. Additionally, thermal hydrolysis pretreatment of sludge prior to anaerobic digestion resulted in increases in DiNP, DiDP, and BBP concentrations. The predicted environmental concentrations for all four compounds in soils after a single biosolids application were calculated and the risk quotients for DEHP in soils were determined. The estimated toxicity risk for DEHP in soils treated with a single application of sludge from any of the six studied WWTPs is lower than the level of concern for acute and chronic risk, as defined by the US EPA.